Preconception midwifery care through a continuity of care approach: A case study - Siska Bradinda Putri Sudirman; Suci Anggina; Aldina Ayunda Insani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Maternal health during the preconception period is an essential determinant in preparing women for healthy pregnancy and reducing maternal risks. Continuity of Care (CoC) is a continuous midwifery care approach that emphasizes comprehensive and individualized services throughout the reproductive life cycle. Purpose: To describe the implementation of continuity of care in preconception midwifery services among four women. Method: This descriptive case study described the implementation of preconception midwifery continuity of care among four women. The study was conducted in the Air Dingin Health Center working area, Padang, from November to December 2025. The subjects consisted of four women in the preconception period. Data collection was carried out through interviews, patient records, and SOAP documentation, while the Varney seven-step management approach was used to describe the continuity of care provided. Results: The findings showed that each client presented different preconception conditions and risk factors requiring individualized interventions. The continuity of care included health screening, communication, information and education, counseling, nutritional guidance, stress management, vaccination education, reproductive planning, and preparation for pregnancy. Continuous midwifery care the care process provided opportunities to identify risk factors and deliver individualized counseling and education of preconception health, supported early identification of maternal risk factors, and encouraged readiness for healthy pregnancy. Conclusion: The implementation of Continuity of Care during the preconception period contributed to describe the implementation through promotive and preventive approaches. Suggestion: Continuous and individualized preconception care is recommended to improve women’s preparedness and support better maternal health outcomes.